Improving the working efficiency of Marketing Department during the pandemic for ABC Company - Li, Xiang (Animo Repository, 2022)
This action research improved the working ineffectiveness in the marketing department during the pandemic by applying the Max Weber bureaucratic management theory and Ryan and Deci’s self-determination theory. The international economy and business model suffered shocks during the COVID-19 pandemic. Employees changed from the traditional working environment face to face to online working from home, which impacted the working effectiveness, efficiency, productivity, and performance of the employees. We applied Max Weber’s bureaucratic management theory in cycle one to help improve the vertical revolution in the marketing department through functional structure and working assignments by using the RACI matrix to improve the redundancy works and complicated management. Meanwhile, we tried to change the leadership to improve the vertical revolution condition and applied the team effectiveness diagnostic to evaluate the action results. Furthermore, we applied Ryan and Deci’s self-determination theory in cycle two to optimize the horizontal revolution in the marketing team, which aims to increase employees’ autonomy, competence, and relatedness through three weeks of online iteration brainstorming meetings. In a broader context, this action research could be taken as a reference by other companies suffering from similar conditions to implement the knowledge and research to address ineffectiveness issues. Moreover, the internal and external industry analysis and the frameworks could help organizations analyze, design, optimize, and implement their products.